Technical and financial feasibility for intensification of the extensive shrimp farming area in Mekong Delta, Vietnam. Issue 1 (22nd December 2021) - Schuur, Anthonie M.; McNevin, Aaron A.; Davis, Robert P.; Boyd, Claude E.; Brian, Susanna; Tinh, Huynh Quoc; Duy, Nguyen Phuong
Abstract: Engineering design studies and financial feasibility assessments were made for construction, maintenance, equipment, operations, loan requirement, shrimp sales and predicted cash flows for simulated transformations of extensive shrimp farms to intensive shrimp farms in the Mekong Delta, Vietnam. Farms with less than 2.8 ha of feed‐based, aerated production ponds would not be profitable at shrimp yields less than 5 t/ha/year. Profit projections increased in response to greater production area on farms and larger annual pond yields. Farms with 6 ha or more of production ponds and yields of 10 t/ha/year or more had the best profit potential. Greater profitability at higher production intensity resulted from a reduction in the labour cost/product weight ratio as yield per unit area increased. Transformation from extensive to intensive farms would allow greater shrimp production, increase worker income and lessen land and water use. Environmental benefits would include a reduction in sediment starvation of the Mekong Delta, and the option to restore some of the several hundred thousand hectares of mangrove area severely degraded by extensive shrimp farming. These two improvements would be of benefit in retarding erosion along the Mekong Delta coastline. The possibility of intensification and consolidation of the shrimp farming area in the Mekong Delta deserves further consideration. Abstract : Extensive shrimp farms have resulted in the loss of a large amount of ecologically critical land within the intertidal zone. The technical feasibility of greatly reducing the area of shrimp farms in the intertidal zone is presented.